Uji Aktivitas Antibakteri Ekstrak Etanol Daun dan Kulit Batang Sawo (Manilkara zapota (L.) Van Royen) - Melzi Octaviani; Syafrina Syafrina (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Sapodilla (Manilkara zapota (L.) van Royen) is a plant that grows in a tropical climate, fruit all year round and the distribution is in the widespread in Indonesia. The contents of secondary metabolites in the leaves and the bark sapodilla are flavonoids, phenols and saponins are known to inhibit the growth of bacteria. The purpose of this research is to know the antibacterial activity of ethanol extract leaves and bark Sapodilla against Staphylococcus aureus and Propionibacterium acnes bacteria. The study was performed by disc diffusion method with the varyation concentrations of ethanol extract from the leaves and bark with a concentration of 50%, 25%, 12.5%, 6.25% and 3.125% respectively and the positive control is clindamycin and the negative control is DMSO . The diameter of the inhibition zone formed on the ethanol extract test of the leaves sapodilla against Staphylococcus aureus and Propionibacterium acnes at a concentration of 50% was 14.18 ± 0.13 mm and 15.33 ± 0.25 mm, respectively. While the diameter of the inhibition zone formed on the ethanol extract test of the bark against Staphylococcus aureus and Propionibacterium acnes at a concentration of 50% was 14.22±0.15 mm and 18.30±0.23 mm, respectively. The results of the data statistical analysis using oneway ANOVA, it shown a significant difference (p < 0.05) between the variation of the concentration of the extract. The test results shown that the antibacterial activity ethanol extract of the leaves and bark of Sapodilla had activity for inhibit the growth of Staphylococcus aureus and Propionibacterium acnes bacteria.